Identification of Genetic Risk Factors for Neonatal Hyperbilirubinemia in Fujian Province, Southeastern China: A Case-Control Study. (12th September 2018) - Zhou, Jinfu; Yang, Changyi; Zhu, Wenbin; Chen, Shuwei; Zeng, Yinglin; Wang, Jing; Zhao, Hong; Chen, Yao; Lin, Feng
Abstract : To date, the genetic risk factors for neonatal hyperbilirubinemia remain unknown in Southeastern China. This case-control study aimed to identify the genetic risk factors for neonatal hyperbilirubinemia in Fujian, Southeastern China. A total of 286 hyperbilirubinemic newborns were enrolled as a case group, and 250 randomly selected newborns without jaundice or with a bilirubin level that was lower than the threshold required for phototherapy served as controls. The serum levels of total bilirubin, unconjugated bilirubin, and direct bilirubin were measured, and the common genetic loci in UGT1A1, OATP1B1, and HO-1 genes were genotyped. Higher incidence of ABO incompatibility and G6PD deficiency was detected in the case group compared to the control group ( P < 0.01). There were significant differences in the frequencies of rs4148323 and rs1805173 genotypes between the case and control groups ( P < 0.05). At the rs4148323 locus, the frequencies of GA heterozygotes and AA mutant homozygotes were higher in the case group than in the control group ( P < 0.05), and at the rs1805173 locus, the frequencies of LS, MS, and SS genotypes were higher in the case group than in the control group ( P < 0.05). A higher frequency of rs4148323 A allele and rs1805173 S allele was detected in the case group compared to the control group ( P = 0). Additionally, multivariate logistic regression analysis identified that the mutant genotype of rs4148323 in the UGT1A1 gene, ABO incompatibility, G6PD deficiency, and SS genotype at rs1805173 locus of the HO-1 gene were genetic risk factors of neonatal hyperbilirubinemia. Our data demonstrate that G211 mutation in the UGT1A1 gene, ABO incompatibility, G6PD deficiency, and the SS genotype of the repeats in the promoter region of the HO-1 gene are risk factors for neonatal hyperbilirubinemia in Fujian, Southeastern China.